SEMIOTICS AS A STANDARD FOR INTERPRETATION OF ISLAMIC TEXTS: STUDIES BASED ON SCIENCE OF BALAGAH AND EXEGESIS - Kamil, Sukron; Handayani, Rizqi; Abdurrosyid, Abdurrosyid (Jurnal Lektur Keagamaan, 2023)
ABSTRACTAmong the problems of Islamic studies is the view of Islamic fundamentalists and conservatives who see semiotics as a theory of the study of texts that is prohibited by Islam. This article discusses Roland Barthes' semiotic theory, both in the sense of denotative/heuristic reading which looks at the text coherently and connotative/hermeneutical reading which requires looking at the social context of the text. The method used is a comparative study of literature, between Barthes' semiotics, bal?gah science (classical Arabic stylistics), and tafsir science. Data was obtained from literature and the results of in-depth interviews with several experts. This article finds that semiotics does not conflict with the Koran, in fact it is a necessity as a standard text study method. Without semiotics, an interpretation of the Koran and hadith is not an Islamic standard interpretation. However, the term known in the Islamic tradition is not semiotics, but na?m. Apart from that, the terms tafsir al-?y?t bi al-?y?t and tafs?r al-?y?t bi al-had?? or vice versa, also the method of interpreting mau??’? (thematic). In interpreting, you are required to master asb?b al-nuz?l, asb?b al-wur?d, and mastery of Meccan and Medina verses as the social context of the text. Semiotics and the study of text studies in Islam, therefore, not only make interpretations of the Al-Qur’an (Islamic texts) that show the intention of the Koran, namely public benefit, but also make Islamic studies scientifically accountable. Keywords: Structural Semiotics, Na?m, Na?w, Bal?gah, Interpretation of al-?y?t bi al-?y?t/bi al-?ad??,| Interpretation of Mau??'?. ABSTRAK Di antara problem kajian keislaman adalah adanya pandangan kaum fundamentalis dan konservatif Islam yang melihat semiotika sebagai teori kajian teks yang dilarang Islam. Artikel ini membahas teori semiotika Roland Barthes, baik dalam arti pembacan denotatif/heuristik yang melihat teks secara koherens maupun pembacaan konotatif/hermeneutis yang mengharuskan melihat konteks sosial teks. Metode yang digunakan adalah studi banding kepustakaan, antara semiotika Barthes, ilmu bal?gah (stilis-tika Arab klasik), dan ilmu tafsir. Data diperoleh dari literatur dan hasil wawancara mendalam terhadap beberapa ahli. Artikel ini menemukan bahwa semiotika tidak bertentangan dengan Al-Qur’an, bahkan merupa¬kan suatu keharusan sebagai metode kajian teks yang baku. Tan¬pa semiotika, sebuah penafsiran atas Al-Qur’an dan hadis bukan sebagai penasiran yang standar secara Islam. Namun, istilah yang dikenal dalam tradisi Islam bukan semiotika, tetapi na?m. Selain itu dikenal juga istilah tafsir al-?y?t bi al-?y?t dan tafs?r al-?y?t bi al-had?? atau sebaliknya, juga metode tafs?r mau??’? (tematik). Dalam melakukan penafsiran diha¬rus¬kan mengua¬sai asb?b al-nuz?l, asb?b al-wur?d, dan penguasaan ayat-ayat Mekah dan Madinah sebagai konteks sosial teks. Semiotika dan studi kajian teks dalam Islam, karenanya, bukan hanya membuat tafsir atas Al-Qur’an (teks-teks Islam) yang memperlihatkan maksud Al-Qur’an, yaitu kemaslahatan publik, melainkan juga menjadikan sebuah kajian Islam bisa dipertanggungjawab¬kan secara ilmiah. Kata kunci: Struktural Semiotik, Na?m, Na?w, Bal?gah, Penafsiran al-?y?t bi al-?y?t/bi al-?ad??, Tafs?r Mau??'?.